1996
DOI: 10.1046/j.1471-4159.1996.66031011.x
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of NG108‐15 Neuroblastoma Cells by Serum Starvation or Dimethyl Sulfoxide Results in Marked Differences in Angiotensin II Receptor Subtype Expression

Abstract: Differentiation of NG108‐15 neuroblastoma cells following exposure to either 1.5% dimethyl sulfoxide (DMSO)/0.5% fetal bovine serum (FBS) or serum starvation resulted in significant differences in angiotensin (AT) receptor levels and the AT1/AT2 receptor ratio. When NG108 cells were differentiated for 4 days with DMSO/low serum, the number of AT binding sites increased 30‐fold compared with the binding levels on undifferentiated (blast) cells. However, cells differentiated by serum starvation for 4 or 14 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 23 publications
0
17
1
Order By: Relevance
“…Interestingly, we could not detect the expression of the C2 insert when Neuro-2a cells were induced to differentiate in the presence of retinoic acid or nerve growth factor. 3 Previously, Seidman et al (35) have shown that DMSO/low serum induced the expression of the angiotensin type 2 receptor, AT2, in neuroblastoma cells, NG108-15. The brain AT system has been shown to be involved in learning and memory as well as growth and development (53)(54)(55)(56).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, we could not detect the expression of the C2 insert when Neuro-2a cells were induced to differentiate in the presence of retinoic acid or nerve growth factor. 3 Previously, Seidman et al (35) have shown that DMSO/low serum induced the expression of the angiotensin type 2 receptor, AT2, in neuroblastoma cells, NG108-15. The brain AT system has been shown to be involved in learning and memory as well as growth and development (53)(54)(55)(56).…”
Section: Discussionmentioning
confidence: 99%
“…To induce differentiation, cells were first cultured in growth medium for 24 h after seeding, and then growth medium was replaced with medium consisting of DMEM with 1.5% DMSO and 0.5% fetal bovine serum (differentiation medium (DM)) according to published protocols (35). For DNA/siRNA transfection, 1 g of plasmid DNA or 33 pmol of siRNA was transfected to 2 ϫ 10 5 undifferentiated Neuro-2a cells using Lipofectamine TM 2000 (Invitrogen).…”
Section: Identification and Quantification Of The C2 Insert In Mousementioning
confidence: 99%
“…[63] Differentiation of NG108-15 was induced by incubating the cells with the films in a serum-free culture medium. [64] By comparing these images with those of cells grown on nanotube films for 3 days in full medium ( Fig. 2), we notice remarkable changes in the morphology of the cells.…”
mentioning
confidence: 93%
“…For the experiments, confluent cultures were harvested with DMEM medium and the cells were seeded into 24-well or 96-well plates and grown for 24 h. Three different media combinations were used: standard (the normal growing medium described above), stress (glucoseand FCS-free) and differentiation medium (0.5% FCS/1.5% DMSO; (Seidman et al 1996).…”
Section: Methodsmentioning
confidence: 99%